PENGARUH PENDIDIKAN KESEHATAN TENTANG STUNTING TERHADAP TINGKAT PENGETAHUAN DAN SIKAP IBU DIDESA BLIMBING NGADIROJO - Ambarwati, Retno; Kristiningtyas, Wahyunti (Jurnal Keperawatan GSH, 2024)
Background: Stunting is a condition of growth failure in children with chronic malnutrition problems caused by a lack of nutritional intake for a long time, resulting in growth disorders in children, namely the child's height is lower or short (dwarf) than the age standard. Stunting that occurs in toddlerhood can increase mortality rates, low cognitive abilities and motor development and unbalanced body functions for adulthood. Therefore, it is necessary to improve nutrition that affects the incidence of stunting. Efforts to improve knowledge and attitudes are carried out through health education which is carried out as an effort to increase mothers' knowledge and attitudes about preventing stunting. Methods: This research method uses a qualitative method with a case study approach, the population in this study is mothers with toddlers in Blimbing Ngadirojo Kidul Village, as many as 30 people. Research Results: The results (pre-test) of the average level of knowledge of respondents were 69% and the results (post-test) of the average level of knowledge of respondents was 95%. Meanwhile, the results (pre-test) of the average attitude level of respondents were 73% and the results (post-test) of the average level of knowledge of respondents was 95%. Conclusion: Respondents experienced an increase in their level of knowledge and attitudes after being given health education about stunting. Thus, providing health education about stunting affects the level of knowledge and attitudes of mothers in the village of Blimbing, Ngadirojo Kidul. Latar Belakang: Stunting adalah kondisi gagal tumbuh pada anak dengan masalah kurang gizi kronis yang disebabkan oleh kurangnya asupan gizi dalam waktu yang cukup lama, sehingga mengakibatkan gangguan pertumbuhan pada anak yakni tinggi badan anak lebih rendah atau pendek (kerdil) dari standar usianya. Stunting yang terjadi pada masa balita dapat meningkatkan angka kematian, kemampuan kognitif dan perkembangan motorik yang rendah serta fungsi tubuh yang tidak seimbang untuk masa dewasanya. Oleh karena itu diperlukan upaya perbaikan gizi yang mempengaruhi kejadian stunting usaha perbaikan pengetahuan dan sikap ini dilakukan melalui pendidikan Kesehatan yang dilakukan sebagai upaya untuk meningkatkan pengetahuan dan sikap ibu tentang pencegahan stunting. Metode: Metode penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus, populasi dalam penelitian ini ibu dengan anak batita diDesa Blimbing Ngadirojo Kidul, sebanyak 30 orang. Hasil Penelitian: Hasil (pre-test) tingkat pengetahuan rata-rata responden 69% dan hasil (post-test) rata-rata tingkat pengetahuan responden adalah 95%. Sedangkan hasil(pre-test) tingkat sikap rata-rata responden 73% dan hasil (post-test) rata-rata tingkat pengetahuan responden adalah 95%. Kesimpulan: Responden mengalami peningkatan tingkat pengetahuan dan sikap setelah diberikan pendidikan kesehatan tentang stunting. Sehingga, pemberian pendidikan kesehatan tentang stunting berpengaruh terhadap tingkat pengetahuan dan sikap ibu didesa blimbing, ngadirojo kidul.